2013
DOI: 10.1002/adfm.201202685
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Tunable Autoclaved Silk‐Tropoelastin Protein Alloys That Control Neuron Cell Responses

Abstract: Tunable protein composites are important for constructing extracellular matrix mimics of human tissues with control of biochemical, structural, and mechanical properties. Molecular interaction mechanisms between silk fibroin protein and recombinant human tropoelastin, based on charge, are utilized to generate a new group of multifunctional protein alloys (mixtures of silk and tropoelastin) with different net charges. These new biomaterials are then utilized as a biomaterial platform to control neuron cell resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 47 publications
4
60
0
Order By: Relevance
“…Recombinant human tropoelastin, displaying a wide range of biological activities, is especially suitable for mediation of the cell responses to biomaterials [2,4–5,2526]. Our results confirmed that the addition of tropoelastin constituents to silk-tropoelastin alloys promoted the attachment of HEFs and the endothelialization by HUVECs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recombinant human tropoelastin, displaying a wide range of biological activities, is especially suitable for mediation of the cell responses to biomaterials [2,4–5,2526]. Our results confirmed that the addition of tropoelastin constituents to silk-tropoelastin alloys promoted the attachment of HEFs and the endothelialization by HUVECs.…”
Section: Discussionsupporting
confidence: 78%
“…For example, optimized silk/tropoelastin ratios for promoting neurite outgrowth of primary cortical neuronal cells (E18) has been determined using a set of autoclave- gelled, compositionally graded protein alloy films. The physical interactions between silk and tropoelastin across hierarchical levels as well as the composition-dependent surface features, including surface charge, roughness and stiffness, have been investigated and linked to neural cell substrate responses [2]. …”
mentioning
confidence: 99%
“…Hydrogels can be of natural or synthetic origin and include agarose (Balgude et al, 2001; Bellamkonda et al, 1995a, 1995b; Cullen et al, 2007a; Dillon et al, 1998; O'Connor et al, 2001), collagen type I (Coates and Nathan, 1987; Coates et al, 1992; Krewson et al, 1994; O'Connor et al, 2000a; O'Shaughnessy et al, 2003), hyaluronic acid (Brännvall et al, 2007, 2007; Hou et al, 2006; Pedron et al, 2013; Tian et al, 2005), N -(2-hydroxypropyl) methacrylamide (HPMA) (Woerly et al, 1990, 1991), poly(ethylene glycol) (PEG) (Pedron et al, 2013; Wang et al, 2014; Zustiak et al, 2013), chitosan (Gao et al, 2014; Leipzig et al, 2011; McKay et al, 2014), alginate (Frampton et al, 2011; Kuo and Chang, 2013; Matyash et al, 2012; Mosahebi et al, 2003), silk fibroin (Benfenati et al, 2010, 2012; Hopkins et al, 2013; Hu et al, 2013; Kim et al, 2010; Tien et al, 2013; Zhang et al, 2012) and methylcellulose (Stabenfeldt and LaPlaca, 2011; Tate et al, 2001), Table 2 .…”
Section: Designing the Ecmmentioning
confidence: 99%
“…A number of cross-linking options are available for the formation of hydrogel scaffolds including traditional chemical cross-linkers, such as glutaraldehyde 104, 114 and bis(sulfosuccinimidyl) suberate (BS3) 115 , to more novel chemical-free cross-linking strategies, such as pH instigated cross-linking 116 and photocrosslinking 117 . Subsequent to the variations in fabrication, tropoelastin, ELP and elastin-based hydrogel scaffolds have demonstrated great tunability in terms of microstructure 118, 119 , mechanical properties 117, 120 , and biological function 121, 122 .…”
Section: Elastin and Tropoelastin: Role In Tissue Repair And Maintmentioning
confidence: 99%